Costs associated with follicular lymphoma among individuals diagnosed with non-Hodgkin lymphoma: a longitudinal analysis using SEER-Medicare data. Issue 1 (2nd January 2020) - Albarmawi, Husam; Nagarajan, Madhuram; Sun, Kai; Gandhi, Aakash Bipin; Yared, Jean; Keating, Karen N.; Appukkuttan, Sreevalsa; Yaldo, Avin; Gharibo, Mecide; Onukwugha, Eberechukwu
Abstract: There is limited information on the cost burden associated with follicular lymphoma (FL) and how it compares to other non-Hodgkin lymphoma (NHL) subtypes. We examined the direct medical costs associated with FL and estimated the incremental 3-year cost of FL compared to other NHL subtypes. Using the linked Surveillance, Epidemiology and End Results-Medicare dataset, we identified 16, 691 NHL patients aged 66 years or older who were diagnosed with NHL between 2007 and 2013. The mean 3-year cost among the full NHL sample was 120, 120 (standard error (SE) 839). The mean 3-year cost per patient was 114, 443 (SE 1738) for FL and 121, 402 (SE 950) for non-FL subtypes. The incremental 3-year cost of FL compared to non-FL was US-5458 (95% confidence interval: US-9325 to US-1590). Longitudinally, FL was less costly than other NHL subtypes in the first year only, and became more expensive in the second and third years.